The effect of addition of ceria on platinum supported on carbon materials in the hydrogenation of ethylene - Maringa, Audacity (My University, 2011)
This study reports the synthesis of carbon materials (carbon nanotubes (CNTs), coiled carbon nanofibers (CCNFs) and carbon spheres (CSs)) using the chemical vapour deposition (CVD) method. The as-synthesized carbon materials were functionalized using nitric acid in order to introduce functional groups and improve the hydrophilic behavior of the carbon materials. Both the as-synthesized and functionalized carbon materials were characterized by TEM, TGA, Raman and FTIR spectroscopy. The presence of functional groups was confirmed by alkalimetry titration and IR spectroscopy data. Ceria (synthesized using the sol-gel method), activated carbon (AC) and titania (P25) were other catalysts supports used and their morphologies were determined by TEM. Platinum was deposited on the various supports to give Pt loadings of 0.5, 1 and 5 % using the polyol method. It was found that small Pt particle sizes were obtained with average particle sizes of 1.8, 2.3, 2.6, 2.9, 2.7 and 1.6 nm for Pt/CCNF, Pt/CNT, Pt/CS, Pt/AC, Pt/CeO2 and Pt/TiO2 respectively at 0.5 % Pt loading. Pt was also deposited on the CeO2/CM supports (5 % and 10 % CeO2 loadings) to make Pt-CeO2/CM catalysts. The Pt supported catalysts were characterized by TEM, EDS, XRD, TPR, BET and TGA. The platinum supported catalysts were tested for the hydrogenation of ethylene. The effect of functionalization of the carbon materials was determined. Pt/functionalized carbon materials had better activity than Pt/as-synthesized carbon materials. On the effects of supports; Pt/TiO2 showed the best activity compared to Pt/CCNF, Pt/CNT, Pt/CS, Pt/AC, Pt/CeO2 and this was attributed to the small Pt sizes formed on TiO2 (Pt mean size was 1.6 nm). An interesting feature in this study was the higher activity of the Pt-CeO2/CM as compared to Pt/CM. This was due to the effect of ceria in preserving the surface area of Pt by suppressing sintering. The effect of increasing the ratio of hydrogen to ethylene was investigated and the findings indicated that all the ethylene was converted to ethane. This was attributed to the fact that at a high hydrogen concentration, the rate of formation of the carbon deposit is slow and the rate of hydrogenation is high. No carbon deposits are thus expected on the Pt catalyst particles. It was found that an increase in the Pt loading resulted in an increase in the rate of reaction.